Short-Term Results of Transforaminal Lumbar Interbody Fusion Using Pedicle Screw with Cortical Bone Trajectory Compared with Conventional Trajectory - Yuji Kasukawa; Naohisa Miyakoshi; Michio Hongo; Yoshinori Ishikawa; Daisuke Kudo; Yoichi Shimada (Asian Spine Journal, 2015)
Study DesignCase-control study.PurposeTo evaluate clinical and radiological results of transforaminal lumbar interbody fusion (TLIF) performed with cortical bone trajectory (CBT) pedicle screw insertion with those of TLIF using 'conventional' or percutaneous pedicle screw insertion.Overview of LiteratureCBT is a new trajectory for pedicle screw insertion in the lumbar spine; clinical and radiological results of TLIF using pedicle screws inserted with CBT are unclear.MethodsIn total, 26 patients (11 males, 15 females) were enrolled in this retrospective study and divided into three groups: TLIF with pedicle screw insertion by conventional minimally invasive methods via the Wiltse approach (M-TLIF, n=10), TLIF with percutaneous pedicle screw insertion (P-TLIF, n=6), and TLIF with pedicle screw insertion with CBT (CBT-TLIF, n=10). Surgical results and preand postoperative radiological findings were evaluated and compared.ResultsIntraoperative blood loss was significantly less with CBT-TLIF (p=0.03) than with M-TLIF. Postoperative lordotic angles did not differ significantly among the three groups. Complete fusions were obtained in 10 of 12 levels (83%) with M-TLIF, in seven levels (100%) with P-TLIF, and in 10 of 11 levels (91%) with CBT-TLIF. On postoperative computed tomography, correct positioning was seen in 84.1% of M-TLIF screws, 88.5% of P-TLIF screws, and 90% of CBT-TLIF screws.ConclusionsCBT-TLIF resulted in less blood loss and a shorter operative duration than M-TLIF or P-TLIF. Postoperative rates of bone union, maintenance of lordotic angles, and accuracy of pedicle screw positions were similar among the three groups.